Exploring the capabilities of modern technologies for health care - Abid Haleem; Mohd Javaid; Rajiv Suman; Raju Vaishya (Apollo Medicine)
Modern technologies offer several new applications and have several benefits in health-care delivery. These technologies include the Internet of things, artificial intelligence, wearable devices, telemedicine, virtual reality, and robotics. These enable targeted personalized health and well-being services. At present, the pharmaceutical industry is confronted with considerable hurdles and financial burdens related to clinical trial, retention, and adherence. Modern technologies allow participation in clinical studies from the comfort of home or any other location as per requirement. In the present digital era, patients can regularly expect more information about their health by using these technologies. These also reduce the chances of errors and precisely evaluate the amount of data and better analysis. Therefore, health-care service providers are now taking a proactive approach by adopting in wearable technology that can enable real-time monitoring of high-risk patients to predict the possibility of a catastrophic health crisis. Telecommunication equipment is more user-friendly and has been utilized by a large population all over the world, which is helpful to reduce the communication gap. In this review, we aimed to identify and discuss the significant capabilities of modern technologies for health-care delivery.